Implementasi Sistem Informasi SIMBA: Analisis Dampak terhadap Efisiensi Pengelolaan Keuangan Zakat dan Tantangan Operasional di BAZNAS Kota Madiun - Indonesia: (Implementation of SIMBA Information System: Impact Analysis on Zakat Financial Management Efficiency and Operational Challenges at BAZNAS Madiun - Indonesia) - Qisma Halimatun Nisa; Anni Izzatul Fauziah; Deril Faradila Ananta; Ade Vanny Noven; Ririn Tri Puspita Ningrum (Al-Muhasib: Journal of Islamic Accounting and Finance, 2025)
Abstract: This study aims to analyze the impact of the BAZNAS Management Information System (SIMBA) on financial efficiency and identify operational challenges at BAZNAS Madiun City, Indonesia. The implementation of digital information systems has become critical for enhancing zakat management efficiency.  A descriptive qualitative used in this study, employing in-depth interviews with SIMBA operators and BAZNAS leadership (n=8), participatory observation, and analysis of financial reports (2020-2024). Data were validated through triangulation and analyzed using thematic techniques.  SIMBA improved financial reporting time efficiency by 67% (average 14 days → 4.5 days) and reduced data input errors by 41%. However, infrastructure disruptions (particularly internet instability) and human resource competency limitations hindered system optimization Reporting transparency increased through real-time fund tracking features for muzakki (zakat payers). SIMBA significantly supports PSAK 109-based zakat management efficiency but requires a strengthened digital infrastructure and continuous HR training programs. These findings provide a reference model for the digital transformation of zakat institutions in rural areas.  Abstrak: Penelitian ini bertujuan menganalisis dampak Sistem Informasi Manajemen BAZNAS (SIMBA) terhadap efisiensi keuangan dan mengidentifikasi tantangan operasional di BAZNAS Kota Madiun. Implementasi sistem informasi digital menjadi penting dalam meningkatkan efisiensi pengelolaan zakat.  Metode yang digunakan adalah studi kualitatif deskriptif melalui wawancara mendalam dengan operator SIMBA dan pimpinan BAZNAS (n=8), observasi partisipatif, serta analisis dokumen laporan keuangan periode 2020-2024. Data divalidasi secara triangulasi dan dianalisis dengan teknik tematik. Hasil penelitian menunjukkan bahwa SIMBA meningkatkan efisiensi waktu pelaporan keuangan sebesar 67% (rata-rata 14 hari → 4.5 hari) dan mengurangi kesalahan input data sebesar 41%. Namun, gangguan infrastruktur (khususnya ketidakstabilan internet) dan keterbatasan kompetensi SDM menghambat optimalisasi sistem. Transparansi pelaporan meningkat melalui fitur pelacakan dana real-time bagi muzakki. Sehingga, SIMBA secara signifikan mendukung efisiensi pengelolaan zakat berbasis PSAK 109, namun memerlukan penguatan infrastruktur digital dan program pelatihan SDM berkelanjutan. Temuan ini menyediakan model referensi bagi transformasi digital lembaga zakat di wilayah pedesaan.